Examining the Mechanical and Thermomechanical Properties of Polymethylmethacrylate Composites Reinforced with Nettle Fibres - DEMİRER, HALİL (SPRINGER HEIDELBERG, 2020)
The aim of this study was to determine the mechanical and thermomechanical properties of nettle fibre-reinforced polymethylmethacrylate composites. The polymethylmethacrylate composites reinforced with nettle fibres were manufactured using nettle fibres obtained using the natural methods. The nettle fibre contents were 0, 2.5, 5, 7.5, and 10 V-f %. The composites so formed were characterized in terms of their mechanical and thermomechanical properties. The mechanical properties of nettle-reinforced composites were characterized in terms of bending stress, bending modulus, impact strength, and fracture toughness tests, whilst their behaviour was determined by heat deviation temperature and Vicat softening temperature. The micro-mechanisms underlying the toughening and fracture processes were observed in the light of studies of the microstructure of fractures. From the mechanical properties of composites reinforced with 10% nettle fibres, an increase of 75% in bending stress, 40% in impact strength, and 106% in fracture toughness was recorded. The findings show that nettle fibres can be used as an important reinforcement material for environmentally friendly composite applications.
Keywords: Composite; Thermal properties; Mechanical properties; Nettle fibre; PMMA; CRYSTALLINE-STRUCTURE; FRACTURE-TOUGHNESS; TENSILE PROPERTIES; FLAX FIBER; CELLULOSE; IMPACT; BIOCOMPOSITES; PERFORMANCE; BEHAVIOR